Possible Thermal Anomalies Associated With Global Terrestrial Earthquakes During 2000–2019 Based on MODIS-LST - Munawar Shah; Muhsan Ehsan; Ayesha Abbas; Arslan Ahmed; Punyawi Jamjareegulgarn (IEEE Geoscience and Remote Sensing Letters, 2021)
The recent advances in satellite-based earthquakes (EQs) precursors provide an opportunity to correlate the seismic variation on lithosphere with atmosphere during the EQ preparation period through a rigorous atmospheric monitoring system. In the present study, seismic-induced thermal anomalies from cloud-free satellite thermal images of Moderate Resolution Imaging Spectroradiometer-Land Surface Temperature (MODIS-LST) are analyzed within a time interval of three months (precedent two months and succeeding one month to each EQ day) of 13 $\text{M}_{w} \ge6.0$ terrestrial EQs during 2000–2019. All these EQs occur in low vegetation and no snow cover regions except $\text{M}_{w}~6.7$ , Siberia Russia event. Remote sensing data show evidence of significant perturbation with reference to confidence bounds in LST within 5–20 time window upon the antecedent and the descendant of EQ day. The studied thermal anomalies are obtained from LST values over the epicenter region. This work endorses the performance of MODIS-LST for detecting EQ-induced thermal anomalies in terrestrial regions with no vegetation and snow cover and also assisting to the development of lithosphere-atmosphere hypothesis over the epicenter region.
Keywords: Earthquake Detection and Analysis; earthquake and tectonic studies; Geological and Geochemical Analysis